The Settlement of Disputes Between The Workers and Wetland Palm Oil Company in the District of Barito Kuala - Yulia Qamariyanti; Ahmad Syauf (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2016)
Barito Kuala District has developedpalm oil plantation sector in wetlands area which gradually changed the pattern of its community life. Previously, most of the people were sharecroppers with the land as their main commodities, then they become the labor because the companies employ people especially from the local community.This research is an empirical legal study to obtain primary data and literature study to obtain secondary data. Its population is the palm oil plantations in Barito Kuala District and the sample is palm oil plantations in wetlands, which employ workers. In relation to the employment, there are sometimes disagreements among the parties which can be caused by a variety of factors. The settlement of the industrial disputes is through stages of the bipartite; the mediation(tripartite); conciliation; arbitration; and the Industrial Relations Court. Industrial Relations Court is the last effort for the disputing parties in industrial relations that can not be resolved through out courts, regulated in Law Number 2 of 2004 concerning Industrial Relations Court .